Isolation and identification of yeasts from local fruits in Thua Thien Hue province, Vietnam - Ho, Thi Xuan Tuy; Nguyen , Thi Kim Cuc; Le, Cong Tuan; Nguyen , Van Phu (Hue University Journal of Science: Natural Science, 2023)
In this study, a total of 30 yeast isolates were recovered from local fruits in Thua Thien Hue province. Genetic characterization based on the ITS sequences identified isolates belonging to 3 species including Saccharomyces cerevisiae, Lachancea fermentati, and Clavispora fructus, with high sequence homology (over 99%) compared to published sequences in the GenBank. All identified S. cerevisiae isolates could grow well at 30°C and ferment several sugar including fructose, galactose, sucrose, mannose, maltose, and raffinose with different performances, but were inhibited at temperature higher than 35°C. The strains also grew well in the medium containing 5% ethanol (v/v) and 200 g/L glucose, but their growth ability was decreased gradually with an increase in ethanol and glucose concentrations. Interestingly, D14 strain was able to grow in the medium supplemented with 12% of ethanol, and 500 g/L of glucose at 45°C, while D7 strain could utilize both mannitol and glycerol at a low level. Our results also indicated that some strains have relatively high sedimentation efficiency, which are favorable conditions for beer fermentation and biomass recovery. The isolated yeast strains with good tolerance properties may provide a potential source of valuable raw materials for applications in beverage production and food processing.